Characterization of Brillouin Scattering Spectrum in LEAF Fiber - Liu, Xuan (Université d'Ottawa / University of Ottawa, 2011)
Fiber optic sensors are designed to measure various parameters. The distributed fiber optics sensor has been a very promising candidate for the structural health monitoring. In this thesis, we characterized LEAF (Large Effective Area Fiber) fiber’s Brillouin scattering spectrum and investigated its potentiality for the distributed Brillouin temperature and strain sensor. Optical fibers with complex refractive index profiles are applied to improve the Brillouin threshold by varying the Brillouin linewidth. As LEAF fiber has a modified refractive index profile, we investigated its Brillouin linewidth’s dependence on the square of the pump light’s frequency. We verified the Brillouin frequency’s variation with input SOP experimentally for LEAF fiber in the spontaneous regime. This sets a limitation for the frequency resolution of distributed Brillouin sensors. We also realized a simultaneous temperature and strain sensor with LEAF fiber applying the Brillouin optical time domain analysis. Based on the direct detection of LEAF beat frequencies, a simultaneous strain and temperature sensor was demonstrated.
Keywords: Fiber optics; Distributed Brillouin Sensor; LEAF fiber; Temperature; Strain